2008
DOI: 10.1021/jp805410c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lewis Acids on Diels−Alder Reaction Reactivity: A Conceptual Density Functional Theory Study

Abstract: Density functional theory (DFT) and conceptual/chemical DFT studies are carried out in this work for the normal electron demand Diels-Alder reaction between isoprene and acrolein to compare chemical reactivity and regioselectivity of the reactants in the absence and presence of Lewis acid (LA) catalysts. A cyclic coplanar structure of acrolein-LA complex has been observed and the natural bond orbital analysis has been employed to interpret the interaction between acrolein and LAs. Reactivity indices from front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 50 publications
(99 reference statements)
1
37
0
Order By: Relevance
“…Parr et al and other researchers [19,[26][27][28]37] suggested that DFT methods and reactivity indices are conceptually insightful and practically convenient to predict the chemical reactivity of molecules. It was anticipated that some reactivity indices are equally important for understanding structural changes.…”
Section: Conceptual Density Functional Theory and Reactivity Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parr et al and other researchers [19,[26][27][28]37] suggested that DFT methods and reactivity indices are conceptually insightful and practically convenient to predict the chemical reactivity of molecules. It was anticipated that some reactivity indices are equally important for understanding structural changes.…”
Section: Conceptual Density Functional Theory and Reactivity Indicesmentioning
confidence: 99%
“…These parameters allow us to measure the inherent quality of an isomer, instead of specific effects in a particular reaction environment [37].…”
Section: Conceptual Density Functional Theory and Reactivity Indicesmentioning
confidence: 99%
“…Lewis acid catalysis of DA reaction has gained considerable attention from both experimental [4][5][6] and theoretical chemists [7][8][9][10][11][12][13][14][15][16]. Lewis acids not only improve the rate of DA reaction, it also helps in achieving high regio-and stereoselectivity compared to the uncatalyzed process [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Energetic results obtained in this study confirms that B3LYP/6-31G(d) method is an excellent compromise between computational cost and accuracy of results for theoretical study of DA reaction. Xia et al [14] studied the impact of AlCl 3 , BCl 3 , FeCl 3 , CoCl 2 , CuCl 2 , CuCl, and ZnCl 2 as Lewis acids in the DA reaction between isoprene and acrolein using both computational and conceptual/chemical DFT [17] based approaches. Use of conceptual DFT based reactivity indices [17,18] has helped in obtaining valuable insights into the role of Lewis acids in DA reactions [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation